Ответ:
1) 8+2√13 и ли 8-2√13
2 178+35√13 или 178-35√13
Решение:
(Составим систему и найдём а из первого ур-я, а b² -из второго уравнения)
![\left \{ {{a+b=5} \atop {ab=3}} \right. \left \{ {{a=5-b} \atop {(5- b)b=3}} \right. \left \{ {{a=5-b} \atop {5b-b^2=3} \right. \left \{ {{a=5-b} \atop {b^2=5b-3}} \right. \left \{ {{a+b=5} \atop {ab=3}} \right. \left \{ {{a=5-b} \atop {(5- b)b=3}} \right. \left \{ {{a=5-b} \atop {5b-b^2=3} \right. \left \{ {{a=5-b} \atop {b^2=5b-3}} \right.](https://tex.z-dn.net/?f=%5Cleft%20%5C%7B%20%7B%7Ba%2Bb%3D5%7D%20%5Catop%20%7Bab%3D3%7D%7D%20%5Cright.%20%5Cleft%20%5C%7B%20%7B%7Ba%3D5-b%7D%20%5Catop%20%7B%285-%20b%29b%3D3%7D%7D%20%5Cright.%20%5Cleft%20%5C%7B%20%7B%7Ba%3D5-b%7D%20%5Catop%20%7B5b-b%5E2%3D3%7D%20%5Cright.%20%5Cleft%20%5C%7B%20%7B%7Ba%3D5-b%7D%20%5Catop%20%7Bb%5E2%3D5b-3%7D%7D%20%5Cright.)
1) а+b²= (5-b)+(5b-3)=4b-2.
Найдём b
-b²+5b-3=0;
D²=5²-4*(-1)*(-3)=25-12=13
b₁=![\frac{-5-\sqrt{13} }{(-1)*2} =\frac{5+\sqrt{13} }{2} \frac{-5-\sqrt{13} }{(-1)*2} =\frac{5+\sqrt{13} }{2}](https://tex.z-dn.net/?f=%5Cfrac%7B-5-%5Csqrt%7B13%7D%20%7D%7B%28-1%29%2A2%7D%20%3D%5Cfrac%7B5%2B%5Csqrt%7B13%7D%20%7D%7B2%7D)
b₂=![\frac{-5+\sqrt{13} }{-2}=\frac{5-\sqrt{13} }{2} \frac{-5+\sqrt{13} }{-2}=\frac{5-\sqrt{13} }{2}](https://tex.z-dn.net/?f=%5Cfrac%7B-5%2B%5Csqrt%7B13%7D%20%7D%7B-2%7D%3D%5Cfrac%7B5-%5Csqrt%7B13%7D%20%7D%7B2%7D)
1)Теперь подставим b1 и b2
а)4b-2=4*(5+√13)/2-2= 2*(5+√13)-2=10+2√13-2=8+2√13
б)4b-2=4*(5-√13)/2-2= 2*(5-√13)-2=10-2√13-2=8-2√13
2)a³b²+a²b³=ab*a(a*b +b²)=3*( 5-b)(3+(5b-3))=15b*(5-b)=75b-b²=75b-(5b-3)=
=75b-5b+3=70b+3.
Теперь подставим b1 и b2
а) 70(5+√13)/2+3=35*5+35√13+3=178+35√13
,)70(5-√13)/2+3=35*5-35√13+3=178-35√13